The noble character-based learning in the ornaments of Kraton Yogyakarta: A visual analysis of Javanese cultural heritage - Ambarwati, Dwi Retno Sri; Rohidi, Tjetjep Rohendi; Syakir, Syakir; Syarif, Muhammad Ibnan; Pamadhi, Hajar (LPMPP Universitas Negeri Yogyakarta, 2024)
In the context of art as a language, ornament also functions as a visual language, because in Javanese culture there is a tradition to express an idea, expression, and moral message containing learning about noble morals through ornamentation. This paper aims to analyze what are the noble moral-based learning contained in ornaments in Kraton Yogyakarta and what influenced them. Data were obtained through field observation, interviews, and literature studies. The results showed that the decorative figural art and ornamentation in Javanese culture are not only visually captivating but also convey profound cultural, religious, and moral meanings, making them an essential part of the Javanese cultural heritage. The visual narrative of ornaments was mainly influenced by cultural acculturation in Javanese society, while noble character-based learning was the result of religious syncretism and belief in Javanese culture.